posted by Madison on .
please how can you solve this problem....... 2(y-6)=3y+12-y
2(y-6) = 3y + 12 - y
Start by combining the y's on the right side.
2(y-6) = 2y + 12
Now do the distributive property on 2(y-6) to get 2y-12. (Both the y and the -6 are multiplied by the outside 2.)
2y - 12 = 2y + 12
Get all the numbers without variables (the y's) on the right side by adding 12 to both sides...
2y = 2y + 24
Combine the y's by subtracting 2y from the right...
0 = 24
That is not correct, so there is no solution.